Social Reflections of the Employment of Recreation Specialists in Turkey - Sefa Şahan Birol; Elif Birol (Türk Spor ve Egzersiz Dergisi)
Recreation specialists are crucial when helping to disseminate recreation to both the needs of the individual and the society. The aim of this study is to examine the increase in employment rates of recreation specialists in Turkey, looking specifically at the economic, social, and psychological dimensions. This research is structured using qualitative research methods and techniques and is designed as theoretical analytical research. A document analysis approach was used when collecting qualitative data, while a descriptive analysis approach was used in the solution of the data. In addition, a reflection on where the research was conducted was discussed within the scope of a potential increase in employment of recreation specialists and the impact it would have on the economic, social, and psychological dimensions of Turkey.